1985
DOI: 10.1152/ajpgi.1985.249.4.g539
|View full text |Cite
|
Sign up to set email alerts
|

Gastric mucosal blood flow measured by laser-Doppler velocimetry

Abstract: To determine the feasibility of measuring gastric mucosal blood flow by laser-Doppler velocimetry (LDV), we utilized two LDV flowmeters to monitor blood flow in mucosa and serosa of chambered canine stomach. In isolated, nonautoregulating gastric segments vasodilated with isoproterenol, LDV mucosal and muscularis blood flows were both linearly related to total electromagnetic blood flow during step increases in perfusion pressure. To assess the depth of the LDV measurement, we recorded reactive hyperemia follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Accordingly, LDF has proven useful for measurement of blood flow changes in the cerebral cortex (6,24), gastrointestinal canal (12,18,21,23),myocardial and skeletal muscle (1,10,14),skin (3,11,26), and renal cortex (22). So far, only a few Received December 30,1991; accepted January 18,1993.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, LDF has proven useful for measurement of blood flow changes in the cerebral cortex (6,24), gastrointestinal canal (12,18,21,23),myocardial and skeletal muscle (1,10,14),skin (3,11,26), and renal cortex (22). So far, only a few Received December 30,1991; accepted January 18,1993.…”
Section: Discussionmentioning
confidence: 99%
“…The laser Doppler technique has been widely used to estimate gastrointestinal mucosal perfusion [7, 19, 20, 21, 22]. After the patient fasted overnight, we performed a routine endoscopic examination and measured the gastric mucosal blood flow (GMBF) by passing the endoscopic probe (PF-309; Perimed, Stockholm, Sweden) of the laser Doppler flowmeter (Periflux PF-3; Perimed) through the biopsy channel of the fiberscope.…”
Section: Methodsmentioning
confidence: 99%
“…In view of conflicting re sults with previous techniques in assessing gastric hemodynamics, newer methods have been used to measure gastric mucosal blood flow in patients with PHG. Laser Doppler flowmetry and reflectance spectrophotometry are two approaches recently validated as reli able techniques to assess gastrointestinal mu cosal perfusion [72,73], Using both methods some investigators have confirmed the pres ence of increased gastric mucosal perfusion in PHG, being greater in patients with severe PHG [12,13]. Contrary to these findings, Iawo et al [74] and Kotzampassi et al [75] reported a reduced gastric mucosal blood flow in patients with PHG.…”
Section: Gastric Mucosai Hemodynamics and Microcirculationmentioning
confidence: 99%